Research on real-time scheduling and collaborative control of collaborative planning of power supply and new energy based on nonlinear programming algorithm in power system - Fangquan, Wu; Yichi, Liu; Xiong, Li (Journal of physics. Conference series, 2025)
With the rapid expansion of the installed scale of new energy(NE), it poses great pressure on the safe and stable operation of power grid (PG), and it is urgent to carry out research on the coordinated development of NE power supply and PG. This paper takes the coordinated development of power generation, transmission and distribution and dispatching as the research object, and adopts the multi-source coordinated development evaluation model of nonlinear programming algorithm in power system to carry out the coordinated evaluation research of the coordinated development of NE sources and regional networks. In the case of balanced access to electricity, wind power is 6.233%, solar photovoltaic power generation is 2.12%, hydropower is 0.835%, and thermal power is 90.812%. This paper is helpful for real-time scheduling of power supply and NE collaborative planning.